Do Expectations Play Any Role in Determining Pak Rupee Exchange Rates? (The Pakistan Development Review, 1997)
This paper presents some evidence on the role of expectations in the determination of Pak rupee exchange rates vis-à-vis the dollar, pound, and yen over the period 1982:1– 1993:7. Results of cointegration and coefficient restriction tests in two out of three cases are supportive of the view of exchange rate determination in postulating that in efficient markets in which uncertainty and expectations about the future are dominant, the equilibrium nominal exchange rate is determined not only by current relative prices but also by the expected real exchange rate. These results are supportive of ex ante purchasing power parity, implying that the real exchange rate follows a random walk. These results also suggest that the anticipated inflation rate is higher in Pakistan than in other countries, which tends to encourage the domestic residents to convert their current balances into foreign currency, so that the terms of trade deteriorate and offset much of gains of the continuous devaluation of Pak rupee by undermining external competitiveness.